High prevalence of Anaplasma marginale in the Crioula Lageana cattle - Mariana da Silva Casa; Julio de M Vettori; Ketriane M de Souza; Luiz Claudio Miletti; Carla Ivane Ganz Vogel; André Luis Ferreira Lima; Joandes Henrique Fonteque (Journal of Infection in Developing Countries)
Introduction: Bovine anaplasmosis is caused by the bacterium Anaplasma marginale; its transmission occurs through vectors such as ticks. Crioula Lageana is a native cattle breed from the South of Brazil used for beef production, with excellent meat quality. There are no studies of the epidemiology of this disease in Crioula Lageana even though tick damage is known to be frequent.